Improving the Accessible Facilities for Disability at Mini Market Kpri, Brawijaya University - Sugiono sugiono; Rio Prasetyo Lukodono; Tanwirul Azhari (Indonesian Journal of Disability Studies, 2018)
Regulation of the Minister of Public Works No. 30 of 2006 on Technical Guidance of Facility and Accessibility on Building and Environment, explains that arrangement of lay-out facility in building must support enough space and circulation for persons with disability and / elderly, including KPRI-UB. KPRI-UB is a shopping place that belongs to the public then it is required to follow the regulation. But in fact, it has not been able to provide adequate access, both from the aspect of facility layout and shelf size. The purpose of this study is to provide proposed layout and proposal size shopping shelves in accordance with the needs of difable consumer in KPRI-UB. The research design used is quantitative with descriptive approach. The result that can be used as a recommendation to design facility which is accessible for difable is change of layout design from shelf contained in KPRI, ramp design, and device used by difables to call help to the operator.